2015
DOI: 10.1111/bjd.13576
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sweating patterns associated with itching, burning and tingling of the skin indicate possible underlying small-fibre neuropathy

Abstract: Patients with burning, itching, numbness and tingling have abnormal sweating patterns and often do not sweat in the symptomatic areas. These novel findings suggest that a small-fibre neuropathy may underlie many cutaneous symptoms and that the neuropathy can be estimated using TST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Indeed, because sweat has been shown to contain various inflammatory cytokines, it is possible that leakage of sweat into the dermis could initiate a complex sequence of events that promotes eczematous inflammation. In view of a recent study indicating that the areas of anhidrosis on thermoregulatory sweat testing correspond to their symptomatic areas, such as itching and strange sensation, itching and strange sensations frequently detected in the AD skin could now be explained by leakage of sweat into the dermis, rather than by small‐fibre neuropathy. Given the efficacy of phototherapy for enhancing barrier function in AD, it is also likely that phototherapy may act to improve AD symptoms by preventing leakage of sweat.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, because sweat has been shown to contain various inflammatory cytokines, it is possible that leakage of sweat into the dermis could initiate a complex sequence of events that promotes eczematous inflammation. In view of a recent study indicating that the areas of anhidrosis on thermoregulatory sweat testing correspond to their symptomatic areas, such as itching and strange sensation, itching and strange sensations frequently detected in the AD skin could now be explained by leakage of sweat into the dermis, rather than by small‐fibre neuropathy. Given the efficacy of phototherapy for enhancing barrier function in AD, it is also likely that phototherapy may act to improve AD symptoms by preventing leakage of sweat.…”
Section: Discussionmentioning
confidence: 94%
“…At the end of the study, 149 patients (66%) had abnormal results and 119 (80%) had anhidrosis at the sites where they had symptoms, suggesting that idiopathic pruritus should be tested to search abnormal sweating [10]. noted dark blue-black discoloration at the side of normal sweating.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in small‐fibre neuropathies is increasing . A group from the Mayo Clinic reported that abnormal sweating, burning, tingling and itch may be indicative of small‐fibre neuropathy.…”
mentioning
confidence: 99%